Autologous Fat Transfer for Scar Prevention and Remodeling: A Randomized, Blinded, Placebo-controlled Trial. Issue 5 (May 2020) - Brown, J. Christian; Shang, Hulan; Yang, Ning; Pierson, Justine; Ratliff, Catherine R.; Prince, Noah; Roney, Nicholas; Chan, Rodney; Hatem, Victoria; Gittleman, Haley; Barnholtz-Sloan, Jill S.; Vincek, Vladimir; et al.
Abstract : Background: Autologous fat transfer—also referred to as fat grafting—has been reported to provide beneficial effects to overlying scar and skin. Despite procedural frequency, there is a paucity of high-level evidence guiding the surgeon in technique, patient selection, and efficacy. Methods: A multicenter, double-blinded, randomized, internally placebo-controlled trial was performed with an aim to qualitatively and quantitatively evaluate the impact of autologous fat transfer on the quality of overlying scar tissue. Fat-grafted scars were evaluated and compared with paired, saline-injected "control" scars. Subjective and objective metrics were evaluated in treated sites for 12 months after treatment. Results: Blinded qualitative results demonstrated a statistically significant improvement in scar quality over time in fat-grafted scars. However, these improvements were not found to be statistically different from changes noted in scars treated with saline. In addition, objective metrics did not statistically differ between saline-injected and autologous fat-grafted scars. Conclusions: Our results demonstrate that autologous fat grafting can improve the qualitative profile of a scar from both the patient and observer perspectives. However, there was no difference in improvement when compared with scars that were treated with saline in a randomized and blinded fashion. These results demonstrate that any improvements in scar quality related to fat grafting are also achieved using saline and suggest that mechanisms other than cell activity may be at play. Additional randomized, blinded, placebo-controlled trials are required to either corroborate or contest the putative beneficial effect(s) of adipose tissue on scar remodeling.